(untitled) (Third Sector Social Economic Review, 2019)
It is impossible to think that a company in a competitive environment stays away from information technologies. Enterprise Resource Planning (ERP) implementation is an information tool that helps restructuring business processes, improving new strategies and application to the enterprise. Enterprise Resource Planning takes over a very important and difficult mission like; human resources, selling, buying, planning, stock management, manufacturing management, distribution, forwarding, financial management, multiple warehouse, multiple structure of factory, international activities, etc. in the organization of the company. In this study, before and after the project in a firm that is presenting in the glass sector, results of the Enterprise Resource Planning implementation that has been came to Turkey in the end of the 1990’s, was taking over with its financial extents and the aim is putting forward the benefits and the differences that Enterprise Resource Planning implementation provided to the company. Data collection process was done via software used with face to face interviews with company managers. It is seen that the firm’s ability to provide the desired benefits from the Enterprise Resource Planning implementation depends on the integration between all functions.